History of Forests in India - Chaturvedi, A. N. (Indian Forester, 1992)
The paper traces the history of India’s forests from around 300 BC to the present, providing an insight into their status during the Muslim and British Periods. Initiation and development of forest conservancy is traced from 1806 onwards. Forest Development after independence is described with special emphasis on conservation and production. The paper recognizes unrestricted use of forests for grazing, lopping and firewood to be the biggest forestry problem in the country. The author apprehends a return to the state of no management of the forests of India soon if corrective measures are not taken by the foresters of the day.